THE ROLE OF THE VILLAGE HEAD AND GOVERNMENT OFFICIALS IN FORMING AN INDEPENDENT VILLAGE (CASE STUDY OF CIBEBER VILLAGE, KIARAPEDES DISTRICT, PURWAKARTA REGENCY) - Rd. Muhammad Ilham Saeful Millah; Selvia Ru'yatus Saefullah; Muhamad Riziq Haikal; Dadan Miftahudin; Fina Lafiyah; Neng Puja Nurmalasari (Bajang Institute, 2023)
The role of the village head , village officials and the entire community is to shape Cibeber village independent village. Building an independent village is not an easy thing, it requires a lot of effort and time . Therefore , collaboration between Heads and Heads is needed village, village officials and all elements of society to make village activities and all village development a success, considering that in Cibeber village itself the enthusiasm of the community is extraordinary in making all village programs a success and mutual cooperation in village development, through the role of the village head who collaborates with the village community to make Cibeber village one of the independent villages in Kiarapedes District , Purwakarta Regency . The research method uses qualitative methods in the form of data analysis technique which consists of three components: data reduction, data presentation and data verification and drawing conclusions. The results and analysis found that the supporting factors for the formation of independent villages include equitable village development, quality human resources, and all village programs can be realized well as well as the role of the village head and participation. the community who assists the village head in development for the development and formation of an Independent Village which influences the progress of the Independent Village in Cibeber Village